Versions of Varro. (November 2020) - Volk, Katharina
Abstract : Is this the Varronian moment? After decades of comparative neglect, especially in Anglophone scholarship, the late republican polymath is suddenly everywhere. There are conferences and conference panels dedicated to his work, some subsequently published as edited volumes. Varro is the subject of dissertations and monographs, either on his own or as a prime exhibit in discussions of such diverse subjects as ancient agricultural writing and late republican religious scholarship. Much needed new editions of his work have appeared or are in preparation. Thus we can look forward to Robert Rodgers' OCT of De re rustica, Giorgio Piras' Teubner of De lingua Latina and a Loeb edition of Varronian fragments by Joseph McAlhany.